1998
DOI: 10.1073/pnas.95.26.15769
|View full text |Cite
|
Sign up to set email alerts
|

Tetracyclines inhibit microglial activation and are neuroprotective in global brain ischemia

Abstract: Ischemic stroke is the most common lifethreatening neurological disease and has limited therapeutic options. One component of ischemic neuronal death is inf lammation. Here we show that doxycycline and minocycline, which are broad-spectrum antibiotics and have antiinf lammatory effects independent of their antimicrobial activity, protect hippocampal neurons against global ischemia in gerbils. Minocycline increased the survival of CA1 pyramidal neurons from 10.5% to 77% when the treatment was started 12 h befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
734
2
8

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 925 publications
(786 citation statements)
references
References 40 publications
33
734
2
8
Order By: Relevance
“…For instance, minocycline is neuroprotective and reduces damage to the blood-brain barrier in models of ischemic stroke by attenuating microglial activation. 18 This effect could be mediated by inhibition of TNF-a production, since a similar protective effect was observed in TNF-a knockout or in wildtype mice that were treated with minocycline prior to the intraparenchymal injection of a dopamine neurotoxin. 28 Minocycline may also have therapeutic benefit for the treatment of HIV-induced neuroinflammation, as minocycline reduced the severity of encephalitis, suppressed viral load in the brain and decreased the expression of brain inflammatory markers in a Simian immunodeficiency model of HIV.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For instance, minocycline is neuroprotective and reduces damage to the blood-brain barrier in models of ischemic stroke by attenuating microglial activation. 18 This effect could be mediated by inhibition of TNF-a production, since a similar protective effect was observed in TNF-a knockout or in wildtype mice that were treated with minocycline prior to the intraparenchymal injection of a dopamine neurotoxin. 28 Minocycline may also have therapeutic benefit for the treatment of HIV-induced neuroinflammation, as minocycline reduced the severity of encephalitis, suppressed viral load in the brain and decreased the expression of brain inflammatory markers in a Simian immunodeficiency model of HIV.…”
Section: Discussionmentioning
confidence: 89%
“…Minocycline has potent anti-inflammatory effects independent from its microbicidal properties, as it is well-known to inhibit macrophage and microglial activation. Of all the tetracyclines, it has the greatest permeability through the blood-brain barrier, 17 and it confers therapeutic benefits in many CNS disease models, including ischemia, 18 Parkinson disease, 19 amyotrophic lateral sclerosis 20 and multiple sclerosis. 17 The tryptophan analog 1-methyltryptophan (1-MT) was chosen for the second approach.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that tetracycline derivatives provide neuroprotection against global brain ischemia (Yrjanheikki et al, 1998), amyotrophic lateral sclerosis (Van Den Bosch et al, 2002), and Parkinson disease (Wu et al, 2002a), and that this neuroprotection involves the inhibition of microglial activation. Recently, a study by Power et al (2003) demonstrated that, in a rat model of ICH, 7-day treatment with minocycline initiated 1 h after collagenase injection protected the morphology of neurons and improved functional recovery.…”
Section: Antimicroglial Activation Strategiesmentioning
confidence: 99%
“…Minocycline was shown to suppress microglial activation and improve neuronal survival after brain ischemia. 228,229 Minocycline and other PARP-1 inhibitors are entering clinical trials for treatment of stroke and other conditions. 230 -232 …”
Section: Other Factors That Influence Proinflammatory Gene Transcriptionmentioning
confidence: 99%